Nursing team performance in child and adolescent sexual violence (Research, Society and Development, 2025)
This research deals with the role of nursing professionals in cases of sexual violence against children and adolescents. To this end, Law No. 8,069/1990 was created, which is provided for in the Statute of the Child and Adolescent, with the purpose of ensuring the protection of this demand, making the State responsible for the applicability of punishments and infractions. Thus, the following objective was constructed: To investigate, in the literature, the performance of the nursing team in the face of sexual violence in children and adolescents. For this purpose, the following methodology was met: Present a Integrative Literature Review (RIL), with a qualitative approach and descriptive nature. To present a Narrative Review of the Literature (NLN), with a qualitative approach and descriptive nature. For the results, we used a search in the database of Latin American and Caribbean Literature on Health Sciences (LILACS) via the Virtual Health Library (VHL) and the Online System for the Search and Analysis of Medical Literature (MEDLINE) via PubMed. Final considerations: the importance of nurses' work in the face of sexual violence against children and adolescents was verified, while before being identified early to the victims of sexual violence, the nursing professional can conduct nursing actions and interventions through individualized care for the victim.